(untitled) - Francis Radice (Tottenham, London, 1993)
This book provides practice in the spoken English. It helps students to talk about and understand banking in English, for example, cheque clearing, EFTPOS or the finance of foreign trade. Each unit of the book has four kinds of activity: 1) Before reading. 2) Short reading passage or dialogue. 3) Vocabulary. 4) Discussion. Sometimes there is also a section on grammar
Keywords: english language - study and teaching